HUBUNGAN COVID-19 TERHADAP MASYARAKAT LANJUT USIA - M.Sultan Fadel Ganie (Jurnal Medika Hutama, 2021)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a type of virus that is pathognomonic of abnormalities in the respiratory system, although this disease worsens or is exacerbated by the comorbidities of infected patients. Elderly people have a high risk of being exposed to COVID-19 disease due to a very significant decrease in the immune system in the elderly community. The result is associated with susceptibility to respiratory tract infections. Reduced mucosal barrier, mucociliary clearance, immune response and the presence of inflammation of the respiratory tract against pathogenic microorganisms are the causes of the immune system not optimal due to immunosense. Decreased ciliary activity in the lungs leads to reduced mucociliary clearance. In addition, the decline in the immune system can be influenced by comorbid diseases that are closely related to COVID-19. This research is a literature study using secondary data obtained from the results of research by previous researchers. Based on the results of a literature study on the relationship between COVID-19 and the elderly, it was stated that there was a significant relationship between individual exposure to COVID-19 and the elderly. The relationship is comparable, meaning that the higher a person's age, the higher the level of exposure to COVID-19, which is influenced by the person's low immunity.